Hematopoietic regeneration under the spell of epigenetic-epitranscriptomic factors and transposable elements. Issue 4 (July 2020) - Clapes, Thomas; Trompouki, Eirini
Abstract : Purpose of review: Since the discovery of master transcription factors that regulate hematopoietic regeneration following different stressors, many more layers of regulation have been discovered. The purpose of this review is to outline the recent discoveries of epigenetic and epitranscriptomic control of hematopoietic regeneration and highlight the novel involvement of transposable elements in this process. Recent findings: Over the past 2 years, we have gained additional knowledge in the role of epigenetic regulators in hematopoietic regeneration. Histone modifiers, like SETD1A, JARID2, KDM6B, and classic DNA methylation regulators, like DNMT3A and TET2, govern hematopoietic regeneration. Concomitantly, the significance of RNA modifications and the expanding functions of transposable elements establish novel layers of regulation of hematopoietic regeneration. Capitalizing on this newly acquired knowledge may provide insights on new therapies or drug targets that will improve or accelerate hematopoietic regeneration. Summary: The spectrum of epigenetic and epitranscriptomic modifications that affect hematopoietic regeneration is continually expanding. Transposable elements are also emerging as potent responders of stress stimuli that affect the self-renewal capacity of hematopoietic stem cells. The future challenge is to understand the hierarchy of these control mechanisms and how they integrate and consolidate information from transcription factors and external stimuli.